Enzymes as Parts in Need of Replacement – and How to Extend Their Working Life. (July 2020) - Tivendale, Nathan D.; Hanson, Andrew D.; Henry, Christopher S.; Hegeman, Adrian D.; Millar, A. Harvey
Abstract : Enzymes catalyze reactions in vivo at different rates and each enzyme molecule has a lifetime limit before it is degraded and replaced to enable catalysis to continue. Considering these rates together as a unitless ratio of catalytic cycles until replacement (CCR) provides a new quantitative tool to assess the replacement schedule of and energy investment into enzymes as they relate to function. Here, we outline the challenges of determining CCRs and new approaches to overcome them and then assess the CCRs of selected enzymes in bacteria and plants to reveal a range of seven orders of magnitude for this ratio. Modifying CCRs in plants holds promise to lower cellular costs, to tailor enzymes for particular environments, and to breed enzyme improvements for crop productivity. Highlights: Enzymes catalyze reactions at very different rates, and measurements or computation estimates are required to accurately determine these rates in vivo . Enzymes each have a half-life determined by their relative rate of degradation, which can be measured in vivo using stable isotopes. Together these rates can be used to constitute a unitless ratio of catalytic cycles until replacement (CCR). CCRs are a new quantitative tool to assess the replacement schedule of enzymes in cells. Challenges of measuring CCRs include isotope incorporation rates, cellular and tissue compartmentation, and the accuracy of metabolic flux measurements and computational calculations. Some of the challenges associated with determining CCRs have been overcome through recent technological advances.